Assessment of Climate Change Impact on Water Footprint of Glutinous Rice (RD6) Production and Adaptation Strategies: A Case Study of Udon Thani Province, Thailand - Suwannakhot C. (2023)
Water is the most important variable in Thailand's agricultural sector. In particular, rice cultivation necessitates a large amount of water during the growing season. Therefore, the objectives of this study were to estimate the water footprint (WF) and the impact of climate change on glutinous rice (RD 6) crop water use (CWU) and to investigate farmers' climate change adaptation strategies in Cha Lae Sub-district, Kumphawapi District, Udon Thani Province. Under rain-fed and irrigated conditions, the CROPWAT8.0 program was used to calculate the WF and CWU values under the SSP245 and SSP585 scenarios based on the CMIP6 model at three time periods: near (2015-2039), mid (2040-2069), and far (2070-2100). The results showed that the total WF values under rain-fed and irrigated conditions in the baseline scenario were 4140.87 m3ton-1 and 3707.10 m3ha-1, respectively. While in the SSP245 and SSP585 scenarios, total CWU values will rise by 1.20 to 6.63% in the near, mid, and far future due to higher temperatures resulting in increased evapotranspiration. Meanwhile, 96.97% of farmers perceived that climate change has been changing, and 81.82% believed climate change had an impact on their farms. The most popular and effective climate change adaptation strategies were increasing irrigation, changing fertilizer application rates, and planting drought-tolerant rice varieties.